Women in the Conflict Zone in Nigeria: A Study of Chibok Girls and A Gift From Darkness - Shah, Usha Kumari (International Journal of Advanced Science and Technology, 2019)
Women of all ages have always endured gender inequalities of one type or another and have been exposed to various forms of discrimination worldwide. Even after years of fighting against the injustice and repression of women, they are still the sufferers who suffer in society due to a lack of respect for their well-being. Armed conflict heavily depends on women’s sexual harassment. Sexual violence becomes a kind of device for torturing innocent people during the time of conflict. Women in war are forced to live a disgraceful life by doing domestic and sexual slave labour. Girls who have been abducted during the time of the fighting are also forced to become wives of the combatants for their reward. This article is a study of the two narratives viz. The Chibok Girls and A Gift From Darkness that bring forth the harrowing experiences of women who became easy victims for the terrorist groups like Boko Haram. Both the narratives based on real incidents, present the condition of women in conflict zone where they are used as pawns in the objectives and missions of the warring groups.